Da tradição à conexão: e, então e aí no domínio da sequenciação retroativo-propulsora no português de Fortaleza - Aguiar, Giselly Kilvia Oliveira (2024)
This research aims to analyze how the items and, then and there are characterized in the domain of propulsive retroactive sequencing in Fortaleza speech. To do this, it is based on the studies on grammaticalization by Heine, Claudi e Hünnemeyer (1991), Hopper and Traugott (2003), and Heine and Kuteva (2007) and on the Domain of Retroactive Propulsive Sequencing, as established by Tavares (1999, 2003). The 944 occurrences, taken from two databases, NORPOFOR - Projeto Norma Oral do Português Popular de Fortaleza - CE and PORCUFORT - Português Oral Culto de Fortaleza, were analyzed in terms of social variables (age, gender and schooling) and linguistic variables (function, semantic class of the verb, discourse articulation, tense and verbal mode), using the AntConc and PSPP software. The analysis showed that: (1) the items e and aí are the most used in Fortaleza speech, predominantly as sequencers; (2) schooling seems to influence the item used: more educated speakers prefer the item e, less educated speakers prefer the item aí; (3) the item aí is the most multifunctional of the items analyzed, appearing in the data in 14 functions; (4) women use the item aí more than men, perhaps because it is a change “without social awareness”; (5) in addition to the discursive functions of the items, pointed out by Tavares (2003), other discursive functions were observed, such as emphatic use and the introducer of an addendum. These results indicate the complexity of the retro-propulsive sequencing domain and the need for further research into the speech community of Fortaleza and other regions in order to reach more reliable conclusions about the use of the items studied, especially the functions observed in this research.